Advances in the Synthesis of Xanthenes: An Overview - Chaudhary, Ankita; Khurana, Jitender M. (Current Organic Synthesis, 2018)
Background: Xanthene is pharmacologically important oxygen containing heterocyclic moeity exhibiting an array of potent biological activities like antibacterial, antiviral, antiinflammatory, antitumor, antioxidant, antiplasmodial etc. Other useful applications of these heterocycles are as fluorescent materials for the visualization of biomolecules and in laser technology. Objective: This review gives an insight of the literature available on the methods for the construction of xanthene nucleus. This review article can be reasonably encouraging for those involved in the synthesis of molecules exhibiting a wide range of biological activities involving xanthene as central nucleus and would provide them assistance in developing new eco-friendly, efficient and economical viable methods. Conclusion: Owing to diverse applications of xanthenes, various synthetic methodologies have been developed, whether to construct this privileged scaffold. Many of the reported methods involve the use of various harsh catalysts/reagents that are not environmentally benign, produce a large amount of waste and need longer reaction times. The sustainable and diversity oriented synthesis of xanthene scaffold which incorporates Green Chemistry tools like multicomponent reaction approach, heterogeneous catalysts, alternate reaction media such as water, ionic liquids, polyethylene glycol etc. has also been developed.
Keywords: Xanthene